A Trust-Based Model For Knowledge Sharing In ERP Adopting Organizations - Moshabbaki, Asghar; Jaha'nyan, Sa'eed (Journal of Knowledge Management Practice, 2009)
There has been a growing interest in examining the factors that support or hinder one's knowledge sharing behavior in the ERP adopting organizations. However, still very few studies examined them from both personal and environmental perspectives. In order to explore the knowledge sharing behaviors within the ERP adopting organizations, this study proposed a social cognitive theory (SCT)-based model that includes knowledge sharing self-efficacy and outcome expectations for personal influences, and multi-dimensional trusts for environmental influences. In order to evaluate the proposed research model, an Iranian ERP adopting company was selected which it's products cover the Iranian market as a developing country. The proposed research model was then evaluated with structural equation modeling, and confirmatory factor analysis was also applied to test if the empirical data conform to the proposed model.
Keywords: Knowledge sharing behavior; ERP adopting organizations; Trust; Self-efficacy; Social cognitive theory